Algebraic Fractions
Algebraic Fractions
Algebraic Fractions
EQUATIONS 2
Can you crack
the code, Mr X?
s
ge
pa
Contents
e
2:01 Further algebraic fractions 2:04 Factorising quadratic trinomials
Fun spot 2:01 An a-MAZE-ing house! 2:05 Quadratic equations
pl
2:02 Expanding and factorising Fun spot 2:05 What did the computer say
Challenge 2:02 Grouping in pairs at lunchtime?
Binomial products Maths terms, Diagnostic test, Assignments
m
2:03
Working Mathematically
• Communicating • Problem Solving • Reasoning • Understanding • Fluency
s
In Year 9 you were shown how to simplify algebraic fractions as well as how to perform the four
ge
basic operations.
The Prep quiz above should have reminded you of these skills. In this section we will extend the
addition and subtraction of fractions to those with pronumerals in the denominator.
pa
Addition and subtraction
When adding or subtracting two fractions you should remember this rule.
e
WORKED EXAMPLE 1
If the denominators are the same, simply add or subtract the numerators.
Sa
2x 3x 2 x + 3x 5 3 5−3
a + = b − =
5 5 5 a a a
1
5x 2
= =
5 a
1
=x
s
When multiplying: • cancel any common factors
ge
• multiply the numerators together and multiply
the denominators together.
When dividing: • turn the second fraction upside down
pa
• multiply as above (i.e. invert and multiply).
When multiplying, add the indices. When dividing, subtract the indices.
e
5+3
5 3
e.g. a × a = a =a 8
e.g. a5 ÷ a3 = a5 − 3 = a2
pl
WORKED EXAMPLES
m
1 1 3 3
2ab 9 2a b 9 x 2y 4 9 x2 y 4 2 9
Sa
1 × = × 2 × 3 2 = × 31 2
3 4b 13 2 4 b1 6 x y 26 x y
a×3
= y2 × 3
1× 2 = Don’t forget
2×x
3a to invert the
= 3y 2 second fraction
2 =
2x when dividing.
‘Invert’ means
1 1 3 1 1 ‘turn upside
2m p 2 3 1 2
2mp 8p 15 m n 3x 15x 3x 4y down’.
3 ÷ = × 4 5 ÷ = ×
5n 15mn 54 31
1 5 n1 4 8 p1 8y 4y 2 8y 5 15 x
m × 3m 1× 1
= =
1× 4 2 y 4 × 5x
3m 2 1
= =
4 10xy 4
s
2a a 5x 2 x 3n n 4 p 3p
e + f + g − h −
ge
3 2 3 4 8 4 5 10
x y 2a 3b 3m n k 2l
i + j − k − l −
4 3 3 2 5 2 6 4
2 4 1 2
pa 7 2 5 1
m + n + o − p −
x 3x 3a 4a 2m 5m 8x 2x
2a 3a x 2x 5m 3m 2x y
q + r − s + t +
e
3x 2 x 3m m 2n 4 n 3a 4a
3 Simplify these products.
pl
x y a b m m a a
a × b × c × d ×
2 3 4 3 2 5 4 10
m
3 4 2 1 1 4 1 1
e × f × g × h ×
a m x y p p n 3n
Sa
p x 2 a m 10 3x 2
i × j × k × l ×
q y a 4 5 n 5 9x
ab 2 x y 6m 15a 8 x 2a
m × n × o × p ×
3 b y x 5a 2m 5 p 3x
4 Simplify these divisions.
m m n n 5a 2a x 3x
a ÷ b ÷ c ÷ d ÷
2 4 3 5 3 9 5 10
5 2 3 1 a 2a 3x x
e ÷ f ÷ g ÷ h ÷
a a 2m 3m b b 5y 10y
a x 2p 8p 10k 2k a a
i ÷ j ÷ k ÷ l ÷
b y 3q 9q 3n 9n 2 3
xy y b ab xy y 9a 4 a
m ÷ n ÷ o ÷ p ÷
2 4 2 6 c cx b 3b
s
4a 3 6x 5z 3 k 3n 2 10kn pq 2 pr 6
g × h 5 × i ×
x 2z 3 3a 2 5k n5 qr 3 p 2q 2r 2
ge
3x 5 9x 3 5m 2 10m 4 3 5
7 a ÷ b ÷ c 3 ÷
2 8 6 pa 9 2y 4y6
4x6 5x 2 5a 3 10a 2 p6 5 p2
d ÷ e ÷ f ÷
3y 5 6y 3b 4 6b 4q5 6q 4
x 6y 2 x4 fg 3 f 3g 5ax 3 15b 2 x 2
g ÷ h ÷ i ÷
z3 yz 5 3h5 6h 2 4by 5 8ay 7
e
pl
without going through any door twice? You can start anywhere, This is harder
inside or outside the house. than it looks!
The Prep quiz above should have reminded you about expanding algebraic expressions.
Each number inside the grouping symbols is multiplied by the term outside.
If we expand the expression 2(x + 4), we obtain 2x + 8. To factorise 2x + 8, we simply reverse this
procedure. We notice that 2 is the highest common factor of 2x and 8, so 2 is written outside the
parentheses and the remainder is written inside the parentheses: 2x + 8 = 2(x + 4).
s
ge
‘Gnidnapxe’ is the
reverse of ‘expanding’.
expand pa
2(x + 4) 2x + 8 It’s ‘factorising’,
you dummy!
factorise
e
pl
This section is a review of these two skills that are needed throughout this chapter. The worked
examples below also include expressions that involve skills used when multiplying with indices.
m
WORKED EXAMPLE 1
Sa
s
Exercise 2:02
ge
Foundation worksheet 2:02A
Grouping symbols
Foundation worksheet 2:02B
Common factors
1 Expand the following.
a a(a + 7) b x(x − 1)
pa c y(2y + 7) d 5p(p − 4)
e 6z(3 + 7z) f 2a(3a − 1) g 4k(2k + 3m) h 8m(n − 3m)
i -2(x + 5) j −7(y − 5) k −(m + 4) l −4(3k − 1)
m -p(p + 1) n -x(x − y) o -2z(3z + 5) p -ab(a − b)
e
2 Simplify:
pl
3 Simplify each expression by expanding the grouping symbols and then collecting like terms.
a 3(x − 2) − 2 (x + 1) b 5(y + 2) + 3(y + 4) c 2(a − 1) + 5(a − 1)
d 8(m − 3) + 5(m + 2) e 4(3x + 2) + 5(x − 4) f 6(x + 7) + 2(2x − 1)
g 5(x − 7) − 3(x − 4) h 6(m + 1) − 3(m + 2) i 9(a + 5) − 7(a − 3)
j 5(n − 5) − 3(n + 7) k x(x + 3) + 3(x + 1) l a(a + 3) + 7(a − 3)
m m(m + 3) − 4(m + 3) n t(t − 5) − 4(t − 5) o a(a + 2b) + a(2a + b)
p x(x − y) + y(x + y)
4 Expand and simplify:
a x2(x2 − 1) b a3(5 − a2) c a2(5a − a3)
d x(x2 + y) e m(7 − m2) f y(y2 − xy)
g 3a2(2a3 + 3a) h 5x(3x2 − x) i 2m3(n2 − m2)
j x(5x2 − 3x + 7) k x2(2x2 + 7x − 14) l y(y2 − 7y − 1)
m a2b3(a3 − b4) n 2x2y(2x3 − 3y4) o 6nm3(2n3m − 5nm4)
p x3(x2 − 3) + 4(x3 + 2) q m3(m3 − 1) − m4(m2 + 2) r z5(z2 − 4) − (z5 − 1)
s
CHALLENGE 2:02 GROUPING IN PAIRS
ge
For some algebraic expressions there may not be a factor common to every term. For example,
there is no factor common to every term in the expression:
3x + 3 + mx + m
pa
The first pair of terms have a common factor of 3 and
the second pair of terms have a common factor of m. So:
e
3x + 3 + mx + m = 3(x + 1) + m(x + 1)
pl
3x + 3 + mx + m = (x + 1)(3 + m)
The original expression has been factorised by grouping the terms in pairs.
Exercises
1 Complete the factorisation of each expression.
a 5(a + 1) + b(a + 1) b 4(y − 3) + x(y − 3) ab + ac + bd + cd = a(b + c) + d(b + c)
c p(q + 7) − 5(q + 7) d m(p + q) + n(p + q) = (b + c)(a + d )
e a(a − b) + b(a − b) f 2x(y + 3) − (y + 3)
2 Factorise these expressions.
These will be
a 6x + 6 + ax + a b 8 p − 8q + mp − mq c ab + 3bc + 5a + 15c
treated further
d x 2 + xy + xz + yz e ab + b + 4a + 4 f 12m 2 + 16m + 3mn + 4 n
in Chapter 10.
g mn − m + n − 1 h x3 + x2 + x + 1 i a 2 + bc + ac + ab
s
Multiplying binomial expressions
ge
The expansion of binomial products may be demonstrated (2a + 6)(a + 9) by areas
by considering the area of a rectangle with dimensions (a + 9)
(2a + 6) and (a + 9).
pa
• The area of the whole rectangle must be equal to the sum
of the four smaller areas.
• Area = (2a + 6)(a + 9) 2a × a 2a × 9
2a
= 2a(a + 9) + 6(a + 9)
e
(2a + 6)
= 2a2 + 18a + 6a + 54
pl
= 2a2 + 24a + 54
• We can see that the product of two binomials has four
m
a 9
WORKED EXAMPLEs
You should notice that each term in
1 (a + 2)(b + 4) = a(b + 4) + 2(b + 4) the first binomial is multiplied by each
= ab + 4a + 2b + 8 term in the second. That set-out
2x2 −15 looks familiar.
2 (a − 2)(a + 7) = a(a + 7) − 2(a + 7)
= a2 + 7a − 2a − 14 (x + 5)(2x − 3)
= a2 + 5a − 14 10x
−3x
3 (x + 2y)(2x + y) = x(2x + y) + 2y(2x + y) = 2x2 + 10x − 3x − 15
2 2
= 2x + xy + 4xy + 2y = 2x2 + 7x − 15
= 2x2 + 5xy + 2y2
4 (1 − x)(x − 3) = 1(x − 3) − x(x − 3) (a + b)(c + d ) = a(c + d ) + b(c + d )
= x − 3 − x2 + 3x = ac + ad + bc + bd
= 4x − x2 − 3
s
c d
e (2x + 1)(2x + 3) f (3n + 2)(2n + 1) g (2x + 3)(4x + 3) h (5t + 2)(2t + 3)
ge
i (2x − 2)(5x − 1) j (8p + 1)(3p − 2) k (5m − 2)(2m − 5) l (3q + 1)(7q − 2)
m (3x + 2)(6x − 2) n (2n + 3)(2n − 3) o (8y − 1)(8y + 1) p (3k − 2)(5k − 3)
q (7p − 1)(7p − 1) r (3x − 1)(5x − 3) s (5x + 4)(5x + 4) t (9y − 4)(3y + 2)
u (5p + 2)(p − 7) v (10q − 1)(q − 10)
pa w (4a + 3)(3a + 4) x (7p + 5)(7p − 5)
4 Expand and simplify:
a (3 + x)(4 + x) b (5 − a)(2 − a) c (7 + m)(1 − m)
d (3 − n)(3 + n) e (4 + y)(y + 5) f (x − 7)(5 − x)
e
trinomials
PREP QUIZ 2:04
Expand: 1 (x + 2)(x + 3) 2 (a − 1)(a + 3) 3 (m − 7)(m − 2)
4 (x + 5)2 5 (a − 2)2
Find two numbers a and b where:
6 a + b = 5 and ab = 6 7 a + b = 9 and ab = 20
8 a + b = -2 and ab = -15 9 a + b = 3 and ab = −4
10 a + b = 7 and ab = -18
s
4x 4
6x 3 8p q4 7
6 p 3q 2 g x3 + 5x2 + 6x
m ÷ n ÷
5y 3 5q4
ge
15y 10 p 6 Solve these equations.
2 Expand, and simplify where possible. a a2 − 36 = 0
a (x − 1)(x + 2) pab 4t2 − 9 = 0
b 5x + 3(x − 1) c m2 + 25 = 0
c 2(x + 3) − 2x − 3 d (x + 2)(x − 3) = 0
d (2x + 1)(x − 7) e (n − 5)(n + 5) = 0
e (x + 5)(x − 5) f (x − 3)2 = 0
e
f (3x + 2)2 g 5w2 − 10w = 0
g x(x − 3) + 2(x + 1) h x2 − 7x + 12 = 0
pl
h (2 − x)(3 − x) i y2 − 4y − 45 = 0
i (x + y)(y − x) j 15 + 8p + p2 = 0
m
j (2x − y)2
7 a Rearrange 10 + 3y − y2 = 0 in the form
k x3(x3 − 1)
0 = y2 − 3y − 10, and then solve the
l 3x2y4(2xy3 + 5x3y)
Sa
equation.
3 Find an expression for the shaded area b Solve the equation:
of this rectangle. Expand and simplify 42 − m − m2 = 0
your answer.
8 Rearrange each equation and solve.
a y2 = 4y + 21
x+1 b n2 + 2n = 80
c z + 110 = z2
2x − 2 d x2 + 5x = 2x + 70
s
d Would the number of 80-year-old men
3 A set of Australian coins consists of a 10c,
suffering from heart disease be greater
ge
20c, 50c, $1 and $2 coin. How many
or less than the number of 80-year-old
different sums of money can be obtained
women suffering from heart disease?
by taking any three of the coins?
Give a reason for your answer.
4 Roger started a trip into the country
pa
between 8 am and 9 am, when the hands of
the clock were together. He arrived at his
destination between 2 pm and 3 pm, when
e
the hands of the clock were exactly 180°
apart. For how long did he travel?
pl
m
Health risks
Sa
Per cent
MALE FEMALE
15
Heart disease
12
Heart
disease
9
Cancer
6
Cancer
Diabetes
3
Diabetes
0
0 10 20 30 40 50 60 70 80 0 10 20 30 40 50 60 70 80
Age
Source: Australian Institute of Health and Welfare
s
a 6·8 cm b
ge
4·8 cm
12·5 cm
5·2 cm
pa
8·6 cm
6 Evaluate: 1:05
e
a 52 × 25 b 45 ÷ 44 c 4-2 d (23)-1
pl
8 Yvonne is paid an hourly rate of $28.40 for a 36 hour week. The first 6 hours 1:07
overtime are paid at time-and-a-half; after that extra hours worked are paid
Sa
double-time. Find Yvonne’s wage for a week in which she works 45 hours.
9 For these triangles, find: 1:11
a the value of x to one decimal place b the value of x to the nearest degree.
65° 10·6 cm
9·7 cm
x°
x cm
6·9 cm
10 For the set of scores 3 5 4 7 5 4 8 3 4, find the: 1:12
a range b mode c median d mean e Q1 f Q3
g interquartile range.